Strategi Pengembangan Bidang Akademik di Pondok Pesantren Darul Hikmah Tulungagung - Pendik Hanafi (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2024)
Realizing the development of educational institutions that will produce competitive graduates, have good morals and have an impact on increasing the quality of Islamic education that can compete and be competitive with other educational institutions. By trying to focus on handling the management of institutions to be better by focusing on development in the academic field. The research method used is qualitative. Data collection techniques are carried out by interviews, observation and documentation. Data collection techniques are by interviews, observation and documentation. Data analysis techniques used are 1) data reduction, 2) data presentation (data displays and 3) conclusion drawing/verification (conclusion drawing/verification). The results of this study are; academic development strategies at the Darul Hikmah Islamic Boarding School in Tulungagung, namely 1) conditions that make progress in the institution; a) effective leadership by creating an institutional vision and implementing it in learning b) empowering quality teachers supported by other teaching staff, c) improving learning resources. 2) views on education a) the ability to distinguish between good and bad in developing institutions b) having the ability to work with anyone, c) the existence of characteristics in the institution. 3) fulfilling policies and the Ministry of Education and society 4) creating a good culture; 5) improving the learning process.